Effect of Dietary Supplementation of Date Palm (Phoenix Dactylifera) Seed Powder on the Growth Performance and Carcass Characteristics of Weaned Rabbits - John, Alagbe (International Journal of Applied and Scientific Research, 2024)
Finding out how date palm (Phoenix dactylifera) seed powder supplementation affects the growth performance and carcass characteristics of weaned rabbits will help to address the increasing cases of antimicrobial resistance and provide natural alternatives to antibiotics. A total of 80 - 5 weeks weaned male crossbred rabbits with an initial body weight of 630.3 ± 2.80 g  were grouped into five treatments (A, B, C, D and E) consisting of twenty rabbits each and each rabbit served as a replicate Phytochemical evaluation of date palm seed powder showed that it contained phenol, flavonoids, terpenoids, tannins, saponins, alkaloids and steroids. Average daily weight gain, average daily feed intake, feed conversion ratio were significantly (P˂0.05) influenced by the treatments. Rabbits fed date palm seed powder at 80 g/kg diet (E) had a higher average body weight and best feed conversion ratio, intermediate in B, C and D, lowest in A. Higher average daily feed intake was recorded among rabbits fed date palm seed powder relative to the control (P˂0.05). Dressed weight values varied from 791.81 - 1000.7 g, dressing percentage (49.02 - 65.80 %) and weights of organs were significantly (P˂0.05) different among the treatments.